Dampak Keberadaan PT Toba Agro Mandiri pada Mata Pencaharian Masyarakat Desa Pohan Julu Kecamatan Siborong-borong, Tapanuli Utara - Juventus Simangunsong; Emi Triani (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2026)
This study examines the impact of the presence of PT Toba Agro Mandiri on the livelihoods of the community in Pohan Julu Village, Siborong-borong District, North Tapanuli Regency. The establishment of the company has brought socio-economic changes to the local community, particularly in relation to employment opportunities and sources of income. Prior to the company's presence, most residents depended on traditional agriculture as their main livelihood. This research aims to analyze the changes in community livelihoods following the operation of the company and to identify the factors that influence the community in responding to these changes. This study uses a descriptive qualitative approach. Data were collected through in-depth interviews, observation, and documentation involving community members and relevant stakeholders. The findings indicate that the presence of PT Toba Agro Mandiri has both positive and negative impacts on the community. Positive impacts include increased income for landowners through land leasing, the availability of new employment opportunities, and the emergence of supporting economic activities. However, negative impacts were also identified, such as unequal access to employment opportunities, social disparities between landowners and non-landowners, and a gradual shift away from traditional agricultural practices. These findings highlight the importance of more inclusive employment opportunities and community empowerment programs to ensure that the benefits of the company's presence can be distributed more evenly among the local community.